Influence of the matrix of aqueous solutions on the adsorption of endocrine disruptors by fullerene C60 - Ion, Ion; Senin, Raluca Madalina; Vasile, Bogdan; Ion, Alina Catrinel (Journal of Environmental Engineering and Landscape Management, 2019)
In this work, fullerene (C60) was selected as a model carbon nanomaterial, humic acid (HA) as the model natural organic matter and bisphenol A (BPA), as a moderate hydrophobic organic contaminant. The effects of ionic strength, concentration of organic matter and of the pH over the adsorption of BPA on C60 were studied, as well as the competition between the BPA and the HA at the active sites of the C60. A possible adsorption mechanism was proposed as well as an attempt to study the sorption process in real environmental samples with characteristics alike to the optimum ones found in the synthetic samples studied.